A Proposed Model of Perceived Support and Entrepreneurial Intentions with Theory of Planned Behavior as Mediator; Case of Omani Youth - Tahir, Muhammad; Kutpudeen, Mohammed; Al Fahdi, Buthania Saif Hamood; Al-Arini, Ahlam Eid Ghashim Hashim; Al Wardi, Shuhd Ibrahim Said (Advances in Social Sciences Research Journal, 2022)
Entrepreneurship intentions among youngsters is a topic of interest in research due to its relevance in understanding the entrepreneurship phenomenon. The current study extends the understanding of entrepreneurship intention by combining the two models namely the Theory of Planned Behavior and the Perceived Support Model. The study is based on a proposed model utilizing the Theory of Planned Behavior components as a mediator between the relationship of the perceived support model and entrepreneurship intention among Omani youngsters. Data collection is based on a cross-sectional survey-based method (n=662) and the analysis is based on AMOS software and consists of two stages. The first stage included testing the reliability and the validity by performing the Confirmatory Factor Analysis and the mediation analysis is performed in the second stage. The results indicate that between the relationship of the perceived support model and the entrepreneurship intention, attitude significantly mediates perceived educational support (β=-.014, P<.05); and perceived structural support (β=.021, P<.05). The relationship of perceived structural support influencing entrepreneurship and mediated by perceived structural support is also significant (β=.019, P<.05). Similarly, perceived behavioral control significantly mediate between perceived structural support (β=.028, P<.05) and entrepreneurship intention. Whereas, the other proposed relationships turned out to be insignificant. Thus, overall, we found partial support for the mediation model. The study recommends that for entrepreneurship intention to be promoted among youngsters, there should be a greater focus on perceived educational support and perceived structural support.